2012
DOI: 10.1007/s10967-012-1723-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 137Cs in benthic plants along depth profiles in the outer Puck Bay (Baltic Sea)

Abstract: A study was conducted on three macroalgae species: Polysiphonia fucoides and Furcellaria lumbricalis, the species of the red algae division, and Cladophora glomerata, representing the green algae division, as well as Zostera marina, representing vascular plants. The main aim of the study was to recognize the level of 137Cs concentrations in the plants, which could be used as a measurement of bioaccumulation efficiency in the selected macrophytes at varying depths, and in the seasonal resolution of the vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Taking into account this short bioaccumulation period, the CF obtained for P. fucoides is unexpectedly high. Analyses of seasonal changes in 137 Cs concentrations in selected macrophytes, conducted in our laboratory, showed that seasonality significantly influenced bioaccumulation efficiency, especially during the vegetation period (Zalewska 2012a(Zalewska , 2012b.…”
Section: Resultsmentioning
confidence: 88%
“…Taking into account this short bioaccumulation period, the CF obtained for P. fucoides is unexpectedly high. Analyses of seasonal changes in 137 Cs concentrations in selected macrophytes, conducted in our laboratory, showed that seasonality significantly influenced bioaccumulation efficiency, especially during the vegetation period (Zalewska 2012a(Zalewska , 2012b.…”
Section: Resultsmentioning
confidence: 88%
“…Filamentous algae or plants with an expanded exterior, which facilitates the exchange of elements with the environment, are at an advantage. Polysiphonia fucoides , a red algae, proved to be one of the best accumulating plants and contained the highest activity concentrations of 137 Cs in consecutive years, and the highest concentration coefficient values [ 26 , 28 , 29 ]. Its bioaccumulation ability towards other radioactive isotopes was confirmed in preliminary laboratory experiments [ 27 ].…”
Section: Introductionmentioning
confidence: 99%